DZIGA VERTOV AND STEVE MANN: THE EMBODIMENT OF THE MASTER METAPHOR OF VISION - Joosse, Angela (eTopia, 2005)
At the intersection of technology and culture, the master metaphor of vision maintains a prominent position. The privileged status of sight in Western culture can be understood as part of the striving to see the world more clearly, to combat distortion and gain an “objective” view. At the turn of the century, new imaging technologies were put into practice as a part of a utopic hope for the future and the modernist project to dispel myth. At the turn of the new millennium, the ubiquitous presence of technologies comprises a controlling system against which we must renew our vision once again. In both contexts, the use of imaging technologies offer liberating possibilities by bringing attention to controlling devices which conspire to remain hidden. Further, theoretical inquiry into the study of technology and culture is often concerned with questions of vision, and approaches are often articulated through metaphors of vision. Within this framework, the writing and practice of both Dziga Vertov (1896-1954) and Steve Mann (1962—) can be studied as embodied approaches to the meeting place of theory, technology and culture.